A Process-Oriented Approach to Learning Process-Oriented Counselling Skills in Groups - Cohen, Avraham (Canadian Journal of Counselling and Psychotherapy, 2007)
This article describes the teaching of process-oriented counselling skills in a group. The interweaving of theory and practice is discussed. The need for and a method of integrating the personal and professional growth of group members with the experiential and conceptual learning of counselling skills are outlined . The congruence of the content and the educational approach is an important element in the training. The development and significance of the community of learners, an intrinsic dimension of the training, are also described.